2000
DOI: 10.1002/1098-2272(200101)20:1<87::aid-gepi8>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Ramifications of HLA class I polymorphism and population genetics for vaccine development

Abstract: HLA polymorphism can complicate the design and development of vaccines, especially those that contain a selected number of epitopes and are directed at pathogens prevalent worldwide. Because of HLA class I restricted antigen recognition and ethnic variation in HLA distribution, such vaccines may not be uniformly effective across populations. We, therefore, considered whether it is possible to assemble a panel of HLA‐A and/or HLA‐B alleles that would allow the formulation of a single vaccine for a set of Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The identification of immunodominant influenza virus-derived peptides presented by a common human MHC class II molecule as we describe in this report will be extremely valuable at several levels for present efforts in vaccine design and in the study of the natural infection of humans with influenza virus. First, there is a great deal of interest in peptide-based vaccines as stable reagents to induce protection against pathogenic organisms such as influenza virus (10,17,33,39,40,76,83). One of the main challenges in the design of peptide-based vaccines is the extent of polymorphism in the human MHC, which in turn influences the degree of coverage that any set of peptides will have in the targeted population.…”
Section: Discussionmentioning
confidence: 75%
“…The identification of immunodominant influenza virus-derived peptides presented by a common human MHC class II molecule as we describe in this report will be extremely valuable at several levels for present efforts in vaccine design and in the study of the natural infection of humans with influenza virus. First, there is a great deal of interest in peptide-based vaccines as stable reagents to induce protection against pathogenic organisms such as influenza virus (10,17,33,39,40,76,83). One of the main challenges in the design of peptide-based vaccines is the extent of polymorphism in the human MHC, which in turn influences the degree of coverage that any set of peptides will have in the targeted population.…”
Section: Discussionmentioning
confidence: 75%
“…Such evolution may gradually alter the genetic composition and responsiveness of populations in greatest need of effective HIV-AIDS vaccines. Consensus through continuous monitoring of disease progression in diverse ethnic groups carefully characterized for their HLA profiles should improve the design of epitope-rich vaccine constructs (9,37,48) and help predict their relative population coverage (58,60). Tables 4 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…The same favorable HLA alleles were overrepresented in canarypox-HIV vaccine recipients with repeatedly detected CTL responses to certain viral proteins (32). These findings imply that HLA typing data may be useful in predicting the relative population coverage (58,60) of epitoperich HIV vaccine constructs (9,37,47).…”
mentioning
confidence: 91%
“…This is particularly in issue in prostate cancer, where African Americans are over-represented, but in whom there is a o20% incidence of the HLA A2.1 allele. 38 We have shown that we are able to cross-present apoptotic material derived from whole prostate tumor cells to DCs for the activation of autologous T cells. This offers the possibility of activating a broad spectrum of potentially tumor reactive T cells, allowing immunization without prior knowledge of specific tumor antigens, yet while presenting any one antigen on multiple HLA molecules.…”
Section: Discussionmentioning
confidence: 99%